2007
DOI: 10.1088/0953-8984/19/37/375109
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of surfactant and nanoparticle self-assembly at liquid–liquid interfaces

Abstract: We have performed molecular dynamics (MD) simulations to investigate self-assembly at water–trichloroethylene (TCE) interfaces with the emphasis on systems containing modified hydrocarbon nanoparticles (1.2 nm in diameter) and sodium dodecyl sulfate (SDS) surfactants. The nanoparticles and surfactants were first distributed randomly in the water phase. The MD simulations have clearly shown the progress of migration and final equilibrium of the SDS molecules at the water–TCE interfaces with the nanoparticles ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 51 publications
3
67
0
Order By: Relevance
“…However, as the concentration increases, adsorption onto the NP surface decreases the surfactant efficiency in lowering the interfacial tension, while concurrently preventing NP aggregation. Luo and Dai, 15 conducting simulations, found that surfactants and NPs compete for adsorption at liquid-liquid interfaces, and that as the surfactant concentration increased the NPs desorb from the interface. The thickness of the interface and the interfacial tension were found to depend significantly on the surfactant concentration, but not so on the NP adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the concentration increases, adsorption onto the NP surface decreases the surfactant efficiency in lowering the interfacial tension, while concurrently preventing NP aggregation. Luo and Dai, 15 conducting simulations, found that surfactants and NPs compete for adsorption at liquid-liquid interfaces, and that as the surfactant concentration increased the NPs desorb from the interface. The thickness of the interface and the interfacial tension were found to depend significantly on the surfactant concentration, but not so on the NP adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular orientations, structural variability of the peptide ring backbones, interfacial molecular areas, and the motion activities of surfactin derivatives were determined [28]. Dai et al reported the MD simulation of the in situ self-assembly of nanoparticles and SDS surfactants at a water/trichloroethylene (TCE) interface, highlighting the potential of using the liquid/liquid interface to produce novel nanomaterials [29]. Rivera et al simulated alkane/water systems containing methanol and reported the surfactant behavior of methanol molecules as they are preferably adsorbed at the interface and reduce the interfacial tension through a rearrangement of the molecules at the interface [30].…”
Section: Introductionmentioning
confidence: 99%
“…Previous simulations have addressed the stability of nanoparticles at interfaces [13][14][15][16][17], interactions between nanoparticles [18], orientational behaviour of anisotropic nanoparticles [17,19], and the self-assembly of nanoparticles at fluid interfaces [20,21]. These simulations have largely focused on the static properties of nanoparticles at interfaces, while only recently has simulation be turned to the dynamic properties of nanoparticles at liquid interfaces [22].…”
Section: Introductionmentioning
confidence: 99%